AN ENHANCED LID ROUTING SECURITY SCHEME FOR MOBILE AD-HOC NETWORKS - Musthafa, Mohamed (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this work we present novel security architecture for MANETs that merges the clustering and the threshold key management techniques. The proposed distributed authentication architecture reacts with the frequently changing topology of the network and enhances the process of assigning the node's public key. In the proposed architecture, the overall network is divided into clusters where the cluster heads (CH) are connected by virtual networks and share the private key of the Central Authority (CA) using Lagrange interpolation. Experimental results show that the proposed architecture reaches to almost 95.5% of all nodes within an ad-hoc network that are able to communicate securely, 9 times faster than other architectures, to attain the same results. Moreover, the solution is fully decentralized to operate in a large-scale mobile network. We also proposing a special security routing architecture called Local Intrusion Detection (LID) to detect Black Hole Attack (BHA) over Ad hoc On Demand Distance Vector (AODV) MANET routing protocol. In LID security routing mechanism, the intrusion detection is performed locally using the previous node of the attacker node instead of performing the intrusion detection via the source node as in Source Intrusion Detection (SID) security routing mechanism. By performing LID security routing mechanism, the security mechanism overhead would be decreased.